Comparative study of representatives of different populations of Sedum roseum (L.) Scop growing in conditions of field crop rotation - O. M. Savchenko; N. S. Tsybulko; T. E. Samatadze (Юг России: экология, развитие)
Aim. Comparative study of the source material of four populations of Sedum roseum (L.) Scop. belonging to different ecological and geographical zones of origin and assessment of their suitability for cultivation in the conditions of the non‐chernozem zone of the Russian Federation.Materials and methods. The following populations were studied: the cultivated population of VILAR (Altai, 1980), the cultivated population of the Botanical Garden of Pitirim Sorokin Syktyvkar State University (Syktyvkar, Komi Republic), an introduced population from Kirovsk, N. A. Avrorin Polar‐Alpine Botanical Garden‐Institute and a cultivated population of Innsbruck Botanical Garden, Austria.Results. Morphological description of the samples was carried out and the productivity of raw materials and seeds and the main biological and karyological features of the populations studied were determined. The results of made it possible to identify Rhodiola populations characterized by high winter hardiness (A and D) and low winter hardiness (B and C). A high productivity of roots and rhizomes in the fourth year of life in populations C and A (30–31 g) was established, and in terms of the content of active substances (phenylpropanoids) in population B (Komi) – 5.4%. The numbers of chromosomes (2n=22) were determined and their morphometric analysis was carried out and formulas of karyotypes of the Rhodiola populations studied were compiled. Chromosomal analysis using C/DAPI‐differential staining showed that no chromosomal abnormalities were detected in the karyotypes, which indicates their stability.Conclusion. Morphological variability indicates the ecological plasticity of the populations studied, which indicates the prospects for their field cultivation.